(untitled) - Asimov, Isaac (New York, 1979)
Contents: Twenty-six essays probe the phenomena of the universe that have shaped and will shape the future of man from the development of multicellular life to twenty possible ways the world could end.
Keywords: Biology,Sinh học; Philosophy,Triết lý